Efficiency assessment of different high-speed tracked vehicle hybrid powertrain conceptions - Ponorac, Luka M.; Blagojević, Ivan A. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Increased development of hybrid powertrains during the last decade brought high-speed tracked vehicles into the same spotlight as commercial and passenger hybrid vehicles. There are several hybrid powertrain conceptions for high-speed tracked vehicles that are mainly researched, but there is still no clear conclusion which conception is the most efficient. The main obstacle for more intense research is the increased difficulty to produce a battery storage system which provides both high power density and protection and shock resistance. However, there is a certain number of research studies and prototypes developed from simulation models that show satisfactory performance for both asymmetric and symmetric hybrid powertrain conceptions. Methods: The developed and verified hybrid simulation model is improved in terms of command signal unit, so that the powertrain and electric motors in the auxiliary drive can easily be operated in the asymmetric hybrid working regime and the symmetric hybrid working regime. The main goal is to simulate specific working regimes where the asymmetric and symmetric hybrid powertrain performance and energy efficiency can be assessed in order to find the most efficient powertrain conception. Results: The results indicate that the asymmetric hybrid powertrain will have less overall power consumption and a more simple control algorithm, because of controlling just one electric motor. For the same overall power, the asymmetric hybrid powertrain has a smaller turning radius, which is satisfactory. When driven in full power, the symmetric hybrid powertrain will have lower turning radius and better manoeuvrability, but serious increase of power consumption. Conclusion: The asymmetric drive has clearly better power efficiency, but the symmetric drive has an advantage of maximum performance. Performing a pivot turn (around the vertical axis), and making a turn without reducing the vehicle velocity is of great importance, especially considering the most common special purpose of this vehicle and manoeuvring in challenging terrain conditions.